A piezoelectric ceramic surface metallization method

By using ferrite-containing casting slurry and magnetron sputtering technology to form the metallization layer on the surface of the piezoelectric ceramic, the problem of insufficient firmness of the metallization layer in the prior art is solved, and the performance of the piezoelectric ceramic and the bonding strength of the metallization layer are significantly improved.

CN119263804BActive Publication Date: 2025-03-14HUNAN MEICHENG NEW MATERIALS TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411809392.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-14
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

In the existing piezoelectric ceramic surface metallization process, the firmness of the metallization layer is poor, which affects the electrical performance, service stability and life of the device.

Method used

Using a piezoelectric ceramic surface metallization method, a cast slurry containing ferrite isostatically laminated with a piezoelectric ceramic body is then used to form a nickel-copper alloy layer and a silver layer on the surface of the composite ceramic sheet by magnetron sputtering.

Benefits of technology

The bonding strength between the metallized layer and the piezoelectric ceramic is improved, and the performance of the piezoelectric ceramic is optimized, especially in terms of crystal structure density and piezoelectric performance improvement.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic metallization, and in particular to a method for metallizing the surface of a piezoelectric ceramic. The method comprises the following steps: firstly preparing a ferrite-containing tape casting slurry, passing the tape casting slurry through a tape casting machine to obtain a tape casting sheet, laminating the tape casting sheet with a piezoelectric ceramic blank and isostatically pressing the blank to obtain a green blank, heating the green blank in a first stage for degreasing, heating the blank in a second stage to 950-1050° C. for sintering for 1-5 hours to obtain a composite ceramic sheet, and finally forming a nickel-copper alloy layer and a silver layer on the surface of the composite ceramic sheet by magnetron sputtering. The piezoelectric ceramic prepared by the invention has excellent piezoelectric performance, and the bonding performance between the metallization layer and the piezoelectric ceramic substrate is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic metallization, in particular to a piezoelectric ceramic surface metallization method. Background Art

[0002] With the rapid development of electronic information technology, piezoelectric ceramic frequency devices have been widely used in audio and video, communications, computer peripherals and other fields. According to statistics, filters and resonators made of piezoelectric ceramics are the two most widely used types of piezoelectric products in civilian electronic products. Piezoelectric ceramic frequency devices are made by performing surface metallization treatment on piezoelectric ceramic substrates and then undergoing multiple processes such as polarization. Among them, the surface metallization of piezoelectric ceramic substrates, that is, preparing a metal electrode layer on the surface of the substrate, is a key process in the production of piezoelectric ceramic frequency devices. The quality of the metal electrode layer will directly affect the device's electrical performance, stability of use, service life, and the pass rate during the processing and manufacturing process.

[0003] At present, the process of metallization treatment of piezoelectric ceramic surface is based on screen printing or vacuum coating. The screen printing method is to directly print the silver electrode slurry on the surface of the piezoelectric ceramic substrate by screen printing, and then prepare it into a metallization layer through processes such as drying and silver burning. The vacuum coating method is a physical process in which the required metal block is placed in the sagger of the vacuum coating machine, and the metal is heated and melted by electricity in the sagger, and then evaporated. After contacting the piezoelectric ceramic substrate, it is deposited on the surface of the substrate to form a metallization layer. However, due to the difference in the properties of piezoelectric ceramics and metals, the screen printing method or vacuum coating method has certain defects, and the firmness of the prepared metallization layer is poor. Summary of the invention

[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes a method for metallizing the surface of piezoelectric ceramics.

[0005] The technical solutions adopted are as follows:

[0006] A piezoelectric ceramic surface metallization method, as follows:

[0007] S1: preparing a piezoelectric ceramic body;

[0008] S2: preparing a tape casting slurry containing ferrite, passing the tape casting slurry through a tape casting machine to obtain a tape casting sheet, laminating the tape casting sheet with a piezoelectric ceramic body and isostatically pressing to obtain a green body;

[0009] S3: After heating the green blank for degreasing in one stage, heating it to 950-1050°C in two stages and sintering it for 1-5h to obtain a composite ceramic sheet;

[0010] S4: Finally, a nickel-copper alloy layer and a silver layer are formed on the surface of the composite ceramic sheet by magnetron sputtering;

[0011] The structural formula of the ferrite is MFe2O4;

[0012] Wherein M is any one of Cu, Zn, Ni and Co;

[0013] The casting slurry comprises the following components in parts by weight:

[0014] 30-50 parts of ferrite, 5-10 parts of polyvinyl butyral, 1-2 parts of polyethylene glycol 400, 1-2 parts of butyl benzyl phthalate, 1-3 parts of triolein, 20-30 parts of ethanol, and 20-30 parts of ethyl acetate.

[0015] Furthermore, the chemical structure formula of the piezoelectric ceramic is as follows:

[0016] [(Na 1 / 2 K 1 / 2 ) 1-x Li x ][Nb 1-y (W 1 / 2 Ce 1 / 2 ) y ]O3-zwt%LaAlO3-uwt%Fe2O3

[0017] Among them, 0<x≤0.1, 0<y≤0.1;

[0018] 1≤z≤5, 1≤u≤5.

[0019] Further, x=0.03, y=0.05.

[0020] Furthermore, z=2, u=1.

[0021] Furthermore, the first stage heating rate is 1-5°C / min, and the second stage heating rate is 10-20°C / min.

[0022] Furthermore, the sintering is performed in a microwave environment.

[0023] Furthermore, the mass ratio of nickel to copper in the nickel-copper alloy layer is 1-9:1-9.

[0024] Furthermore, the thickness of the nickel-copper alloy layer is 0.5-1 μm, and the thickness of the silver layer is 0.1-0.5 μm.

[0025] Beneficial effects of the present invention:

[0026] The present invention provides a method for metallizing the surface of piezoelectric ceramics. Doping Li at the A position of KNN ceramics can cause changes in the crystal structure. By controlling the doping amount of Li, the orthorhombic phase and the tetragonal phase coexist, thereby optimizing the performance of the piezoelectric ceramics. The electronegativity of the doped Li at the B position of KNN ceramics is stronger than that of Nb.5+ W 1 / 2 Ce 1 / 2 ) 5+ Composite ions can maintain the B-site electron conservation state, make the crystal structure of the ceramic more compact and produce lattice distortion, which plays a positive role in improving the piezoelectric performance. LaAlO3 has a perovskite structure and can form a multi-component solid solution with a quasi-isotropic phase boundary with KNN ceramics. Near the quasi-isotropic phase boundary component, under the action of an external electric field or stress, the spontaneous polarization becomes easier to change direction, and the piezoelectric performance will be greatly improved. The properties of ferrite are between ceramics and metals, with certain electrical conductivity and unique magnetic and electrical properties. Using it as a transition layer can effectively promote the bonding between piezoelectric ceramics and metallization layer materials, and effectively alleviate the thermal stress caused near the interface due to the large difference in the expansion coefficients of the two materials, thereby improving the bonding strength between the metallization layer and the piezoelectric ceramic. At present, there are no reports on using ferrite as a ceramic metallization transition layer. DETAILED DESCRIPTION

[0027] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0028] Embodiment 1:

[0029] This embodiment provides a piezoelectric ceramic surface metallization method:

[0030] According to the general formula [(Na 1 / 2 K 1 / 2 ) 0.97 Li 0.03 ][Nb 0.95 (W 1 / 2 Ce 1 / 2 ) 0.05 ] Na2CO3, K2CO3, Li2CO3, Nb2O5, WO3, CeO2, LaAlO3 and Fe2O3 are weighed in the stoichiometric ratio of O3-2wt% LaAlO3-1wt% Fe2O3 and added into a ball mill, with anhydrous ethanol as the ball milling medium, mixed and ball milled in a planetary ball mill for 10 hours, dried in an oven, and then pre-sintered at 800°C for 2 hours to obtain a preformed powder, the preformed powder is added into a ball mill, with anhydrous ethanol as the ball milling medium, mixed and ball milled again in a planetary ball mill for 10 hours, dried in an oven, a polyvinyl alcohol aqueous solution with a mass concentration of 8wt% is added as a binder and granulated, the granules obtained after passing through an 80-mesh sieve are added into a mold, and pressed at 100MPa to obtain a piezoelectric ceramic body;

[0031] 40 parts by weight of ferrite NiFe2O4, 8 parts by weight of polyvinyl butyral, 1 part by weight of polyethylene glycol 400, 1 part by weight of butyl benzyl phthalate, 2 parts by weight of triolein, 30 parts by weight of ethanol and 30 parts by weight of ethyl acetate were added into a ball mill, mixed and ball-milled in a planetary ball mill for 5 hours to obtain a casting slurry, the casting slurry was passed through a casting machine to obtain a casting sheet with a thickness of 10 μm, two casting sheets and a piezoelectric ceramic body were laminated and isostatically pressed at 100 MPa in a "sandwich" structure to obtain a green blank;

[0032] The green blank was placed in a microwave sintering furnace and heated to 600°C at a speed of 1°C / min for 2 hours for degreasing. Then, the microwave was turned on and heated to 1050°C at a speed of 10°C / min for 3 hours to obtain a composite ceramic sheet. The frequency and power of the microwave sintering furnace were 2.45 GHz and 1.1 kW respectively.

[0033] Finally, a nickel-copper alloy layer with a thickness of 0.5 μm and a silver layer with a thickness of 0.2 μm were formed on the upper and lower surfaces of the composite ceramic sheet by magnetron sputtering. The magnetron sputtering used a nickel-copper alloy target and a pure silver target with a mass ratio of 1:1. When the vacuum degree of the sputtering studio reached 3×10 -2 Pa, start to fill with argon gas, and adjust the argon gas flow rate to keep the vacuum degree at 8±0.5×10 -1 Pa, the current when sputtering nickel-copper alloy target is 7A, the time is 13 min, the current when sputtering pure silver target is 7A, the time is 6 min, after the single-sided sputtering is completed, the loading fixture is automatically turned over, and the nickel-copper layer and silver layer are sputtered on the other side with the same sputtering conditions.

[0034] The tensile strength of the silver layer was measured to be 25.6 MPa according to the method in 4.5.19 of GJB 3522A-2011.

[0035] Embodiment 2:

[0036] This embodiment provides a piezoelectric ceramic surface metallization method:

[0037] According to the general formula [(Na 1 / 2 K 1 / 2 ) 0.97 Li 0.03 ][Nb 0.95 (W 1 / 2 Ce 1 / 2 ) 0.05] Na2CO3, K2CO3, Li2CO3, Nb2O5, WO3, CeO2, LaAlO3 and Fe2O3 are weighed in the stoichiometric ratio of O3-2wt% LaAlO3-1wt% Fe2O3 and added into a ball mill, with anhydrous ethanol as the ball milling medium, mixed and ball milled in a planetary ball mill for 10 hours, dried in an oven, and then pre-sintered at 800°C for 2 hours to obtain a preformed powder, the preformed powder is added into a ball mill, with anhydrous ethanol as the ball milling medium, mixed and ball milled again in a planetary ball mill for 10 hours, dried in an oven, a polyvinyl alcohol aqueous solution with a mass concentration of 8wt% is added as a binder and granulated, the granules obtained after passing through an 80-mesh sieve are added into a mold, and pressed at 100MPa to obtain a piezoelectric ceramic body;

[0038] 30 parts by weight of ferrite NiFe2O4, 5 parts by weight of polyvinyl butyral, 1 part by weight of polyethylene glycol 400, 1 part by weight of butyl benzyl phthalate, 1 part by weight of triolein, 30 parts by weight of ethanol and 30 parts by weight of ethyl acetate were added into a ball mill, mixed and ball-milled in a planetary ball mill for 5 hours to obtain a casting slurry, the casting slurry was passed through a casting machine to obtain a casting sheet with a thickness of 10 μm, two casting sheets and a piezoelectric ceramic body were laminated and isostatically pressed at 100 MPa in a "sandwich" structure to obtain a green blank;

[0039] The green blank was placed in a microwave sintering furnace and heated to 600°C at a speed of 1°C / min for 2 hours for degreasing. Then, the microwave was turned on and heated to 1050°C at a speed of 10°C / min for 3 hours to obtain a composite ceramic sheet. The frequency and power of the microwave sintering furnace were 2.45 GHz and 1.1 kW respectively.

[0040] Finally, a nickel-copper alloy layer with a thickness of 0.5 μm and a silver layer with a thickness of 0.2 μm were formed on the upper and lower surfaces of the composite ceramic sheet by magnetron sputtering. The magnetron sputtering used a nickel-copper alloy target and a pure silver target with a mass ratio of 1:1. When the vacuum degree of the sputtering studio reached 3×10 -2 Pa, start to fill with argon gas, and adjust the argon gas flow rate to keep the vacuum degree at 8±0.5×10 -1 Pa, the current when sputtering nickel-copper alloy target is 7A, the time is 13 min, the current when sputtering pure silver target is 7A, the time is 6 min, after the single-sided sputtering is completed, the loading fixture is automatically turned over, and the nickel-copper layer and silver layer are sputtered on the other side with the same sputtering conditions.

[0041] The tensile strength of the silver layer was measured to be 23.3 MPa according to the method in 4.5.19 of GJB 3522A-2011.

[0042] Embodiment 3:

[0043] This embodiment provides a piezoelectric ceramic surface metallization method:

[0044] According to the general formula [(Na 1 / 2 K 1 / 2 ) 0.97 Li 0.03 ][Nb 0.95 (W 1 / 2 Ce 1 / 2 ) 0.05 ] Na2CO3, K2CO3, Li2CO3, Nb2O5, WO3, CeO2, LaAlO3 and Fe2O3 are weighed in the stoichiometric ratio of O3-2wt% LaAlO3-1wt% Fe2O3 and added into a ball mill, with anhydrous ethanol as the ball milling medium, mixed and ball milled in a planetary ball mill for 10 hours, dried in an oven, and then pre-sintered at 800°C for 2 hours to obtain a preformed powder, the preformed powder is added into a ball mill, with anhydrous ethanol as the ball milling medium, mixed and ball milled again in a planetary ball mill for 10 hours, dried in an oven, a polyvinyl alcohol aqueous solution with a mass concentration of 8wt% is added as a binder and granulated, the granules obtained after passing through an 80-mesh sieve are added into a mold, and pressed at 100MPa to obtain a piezoelectric ceramic body;

[0045] 30 parts by weight of ferrite NiFe2O4, 10 parts by weight of polyvinyl butyral, 1 part by weight of polyethylene glycol 400, 2 parts by weight of butyl benzyl phthalate, 1 part by weight of triolein, 30 parts by weight of ethanol and 30 parts by weight of ethyl acetate were added into a ball mill, mixed and ball-milled in a planetary ball mill for 5 hours to obtain a casting slurry, the casting slurry was passed through a casting machine to obtain a casting sheet with a thickness of 10 μm, two casting sheets and a piezoelectric ceramic body were laminated and isostatically pressed at 100 MPa in a "sandwich" structure to obtain a green blank;

[0046] The green blank was placed in a microwave sintering furnace and heated to 600°C at a speed of 1°C / min for 2 hours for degreasing. Then, the microwave was turned on and heated to 1050°C at a speed of 10°C / min for 3 hours to obtain a composite ceramic sheet. The frequency and power of the microwave sintering furnace were 2.45 GHz and 1.1 kW respectively.

[0047] Finally, a nickel-copper alloy layer with a thickness of 0.5 μm and a silver layer with a thickness of 0.2 μm were formed on the upper and lower surfaces of the composite ceramic sheet by magnetron sputtering. The magnetron sputtering used a nickel-copper alloy target and a pure silver target with a mass ratio of 1:1. When the vacuum degree of the sputtering studio reached 3×10 -2 Pa, start to fill with argon gas, and adjust the argon gas flow rate to keep the vacuum degree at 8±0.5×10 -1 Pa, the current when sputtering nickel-copper alloy target is 7A, the time is 13 min, the current when sputtering pure silver target is 7A, the time is 6 min, after the single-sided sputtering is completed, the loading fixture is automatically turned over, and the nickel-copper layer and silver layer are sputtered on the other side with the same sputtering conditions.

[0048] The tensile strength of the silver layer was measured to be 22.8 MPa according to the method in 4.5.19 of GJB 3522A-2011.

[0049] Embodiment 4:

[0050] This embodiment provides a piezoelectric ceramic surface metallization method:

[0051] According to the general formula [(Na 1 / 2 K 1 / 2 ) 0.97 Li 0.03 ][Nb 0.95 (W 1 / 2 Ce 1 / 2 ) 0.05 ] Na2CO3, K2CO3, Li2CO3, Nb2O5, WO3, CeO2, LaAlO3 and Fe2O3 are weighed in the stoichiometric ratio of O3-2wt% LaAlO3-1wt% Fe2O3 and added into a ball mill, with anhydrous ethanol as the ball milling medium, mixed and ball milled in a planetary ball mill for 10 hours, dried in an oven, and then pre-sintered at 800°C for 2 hours to obtain a preformed powder, the preformed powder is added into a ball mill, with anhydrous ethanol as the ball milling medium, mixed and ball milled again in a planetary ball mill for 10 hours, dried in an oven, a polyvinyl alcohol aqueous solution with a mass concentration of 8wt% is added as a binder and granulated, the granules obtained after passing through an 80-mesh sieve are added into a mold, and pressed at 100MPa to obtain a piezoelectric ceramic body;

[0052] 40 parts by weight of ferrite CuFe2O4, 8 parts by weight of polyvinyl butyral, 1 part by weight of polyethylene glycol 400, 1 part by weight of butyl benzyl phthalate, 2 parts by weight of triolein, 30 parts by weight of ethanol and 30 parts by weight of ethyl acetate were added into a ball mill, mixed and ball-milled in a planetary ball mill for 5 hours to obtain a casting slurry, the casting slurry was passed through a casting machine to obtain a casting sheet with a thickness of 10 μm, two casting sheets and a piezoelectric ceramic body were laminated and isostatically pressed at 100 MPa in a "sandwich" structure to obtain a green blank;

[0053] The green blank was placed in a microwave sintering furnace and heated to 600°C at a speed of 1°C / min for 2 hours for degreasing. Then, the microwave was turned on and heated to 1050°C at a speed of 10°C / min for 3 hours to obtain a composite ceramic sheet. The frequency and power of the microwave sintering furnace were 2.45 GHz and 1.1 kW respectively.

[0054] Finally, a nickel-copper alloy layer with a thickness of 0.5 μm and a silver layer with a thickness of 0.2 μm were formed on the upper and lower surfaces of the composite ceramic sheet by magnetron sputtering. The magnetron sputtering used a nickel-copper alloy target and a pure silver target with a mass ratio of 1:1. When the vacuum degree of the sputtering studio reached 3×10 -2 Pa, start to fill with argon gas, and adjust the argon gas flow rate to keep the vacuum degree at 8±0.5×10 -1 Pa, the current when sputtering nickel-copper alloy target is 7A, the time is 13 min, the current when sputtering pure silver target is 7A, the time is 6 min, after the single-sided sputtering is completed, the loading fixture is automatically turned over, and the nickel-copper layer and silver layer are sputtered on the other side with the same sputtering conditions.

[0055] The tensile strength of the silver layer was measured to be 20.5 MPa according to the method in 4.5.19 of GJB 3522A-2011.

[0056] Comparative Example 1:

[0057] The method is basically the same as Example 1, except that it does not contain a cast sheet layer, that is, the piezoelectric ceramic body is directly sintered and then magnetron sputtered;

[0058] This comparative example provides a piezoelectric ceramic surface metallization method:

[0059] According to the general formula [(Na 1 / 2 K 1 / 2 ) 0.97 Li 0.03 ][Nb 0.95 (W 1 / 2 Ce 1 / 2 ) 0.05 ] Na2CO3, K2CO3, Li2CO3, Nb2O5, WO3, CeO2, LaAlO3 and Fe2O3 are weighed in the stoichiometric ratio of O3-2wt% LaAlO3-1wt% Fe2O3 and added into a ball mill, with anhydrous ethanol as the ball milling medium, mixed and ball milled in a planetary ball mill for 10 hours, dried in an oven, and then pre-sintered at 800°C for 2 hours to obtain a preformed powder, the preformed powder is added into a ball mill, with anhydrous ethanol as the ball milling medium, mixed and ball milled again in a planetary ball mill for 10 hours, dried in an oven, a polyvinyl alcohol aqueous solution with a mass concentration of 8wt% is added as a binder and granulated, the granules obtained after passing through an 80-mesh sieve are added into a mold, and pressed at 100MPa to obtain a piezoelectric ceramic body;

[0060] The piezoelectric ceramic body was placed in a microwave sintering furnace and heated to 600°C at a speed of 1°C / min for 2 hours for degreasing. The microwave was then turned on and heated to 1050°C at a speed of 10°C / min for 3 hours to obtain a ceramic sheet. The frequency and power of the microwave sintering furnace were 2.45 GHz and 1.1 kW, respectively.

[0061] Finally, a nickel-copper alloy layer with a thickness of 0.5 μm and a silver layer with a thickness of 0.2 μm were formed on the upper and lower surfaces of the ceramic sheet by magnetron sputtering. The magnetron sputtering used a nickel-copper alloy target and a pure silver target with a mass ratio of 1:1. When the vacuum degree of the sputtering studio reached 3×10 -2 Pa, start to fill with argon gas, and adjust the argon gas flow rate to keep the vacuum degree at 8±0.5×10 -1 Pa, the current when sputtering nickel-copper alloy target is 7A, the time is 13 min, the current when sputtering pure silver target is 7A, the time is 6 min, after the single-sided sputtering is completed, the loading fixture is automatically turned over, and the nickel-copper layer and silver layer are sputtered on the other side with the same sputtering conditions.

[0062] The tensile strength of the silver layer was measured to be 13.2 MPa according to the method in 4.5.19 of GJB 3522A-2011.

[0063] Comparative Example 2:

[0064] The same as Example 1, except that LaAlO is not added during the preparation of the piezoelectric ceramic. 3;

[0065] This comparative example provides a piezoelectric ceramic surface metallization method:

[0066] According to the general formula [(Na 1 / 2 K 1 / 2 ) 0.97 Li 0.03 ][Nb 0.95 (W 1 / 2 Ce 1 / 2 ) 0.05 ]O3-1wt%Fe2O3 in a stoichiometric ratio; weigh Na2CO3, K2CO3, Li2CO3, Nb2O5, WO3, CeO2, and Fe2O3 and add them to a ball mill; use anhydrous ethanol as a ball milling medium; mix and ball mill them in a planetary ball mill for 10 hours, then dry them in an oven; and then pre-sinter them at 800°C for 2 hours to obtain a preformed powder; add the preformed powder to a ball mill; use anhydrous ethanol as a ball milling medium; mix and ball mill them again in a planetary ball mill for 10 hours, then dry them in an oven; add a polyvinyl alcohol aqueous solution with a mass concentration of 8wt% as a binder and granulate them; add the granules obtained after passing through an 80-mesh sieve into a mold; and press them at 100MPa to obtain a piezoelectric ceramic body;

[0067] 40 parts by weight of ferrite NiFe2O4, 8 parts by weight of polyvinyl butyral, 1 part by weight of polyethylene glycol 400, 1 part by weight of butyl benzyl phthalate, 2 parts by weight of triolein, 30 parts by weight of ethanol and 30 parts by weight of ethyl acetate were added into a ball mill, mixed and ball-milled in a planetary ball mill for 5 hours to obtain a casting slurry, the casting slurry was passed through a casting machine to obtain a casting sheet with a thickness of 10 μm, two casting sheets and a piezoelectric ceramic body were laminated and isostatically pressed at 100 MPa in a "sandwich" structure to obtain a green blank;

[0068] The green blank was placed in a microwave sintering furnace and heated to 600°C at a speed of 1°C / min for 2 hours for degreasing. Then, the microwave was turned on and heated to 1050°C at a speed of 10°C / min for 3 hours to obtain a composite ceramic sheet. The frequency and power of the microwave sintering furnace were 2.45 GHz and 1.1 kW respectively.

[0069] Finally, a nickel-copper alloy layer with a thickness of 0.5 μm and a silver layer with a thickness of 0.2 μm were formed on the upper and lower surfaces of the composite ceramic sheet by magnetron sputtering. The magnetron sputtering used a nickel-copper alloy target and a pure silver target with a mass ratio of 1:1. When the vacuum degree of the sputtering studio reached 3×10 -2 Pa, start to fill with argon gas, and adjust the argon gas flow rate to keep the vacuum degree at 8±0.5×10 -1 Pa, the current when sputtering nickel-copper alloy target is 7A, the time is 13 min, the current when sputtering pure silver target is 7A, the time is 6 min, after the single-sided sputtering is completed, the loading fixture is automatically turned over, and the nickel-copper layer and silver layer are sputtered on the other side with the same sputtering conditions.

[0070] The tensile strength of the silver layer was measured to be 20.6 MPa according to the method in 4.5.19 of GJB 3522A-2011.

[0071] Comparative Example 3:

[0072] The same as Example 1, except that Fe2O is not added during the preparation of the piezoelectric ceramic. 3;

[0073] This embodiment provides a piezoelectric ceramic surface metallization method:

[0074] According to the general formula [(Na 1 / 2 K 1 / 2 ) 0.97 Li 0.03 ][Nb 0.95 (W 1 / 2 Ce 1 / 2 ) 0.05]O3-2wt%LaAlO3 in a stoichiometric ratio; weigh Na2CO3, K2CO3, Li2CO3, Nb2O5, WO3, CeO2, and LaAlO3 and add them to a ball mill; use anhydrous ethanol as a ball milling medium; mix and ball mill them in a planetary ball mill for 10 hours, then dry them in an oven; and then pre-sinter them at 800°C for 2 hours to obtain a preformed powder; add the preformed powder to a ball mill; use anhydrous ethanol as a ball milling medium; mix and ball mill them again in a planetary ball mill for 10 hours, then dry them in an oven; add a polyvinyl alcohol aqueous solution with a mass concentration of 8wt% as a binder and granulate them; add the granules obtained after passing through an 80-mesh sieve into a mold; and press them at 100MPa to obtain a piezoelectric ceramic body;

[0075] 40 parts by weight of ferrite NiFe2O4, 8 parts by weight of polyvinyl butyral, 1 part by weight of polyethylene glycol 400, 1 part by weight of butyl benzyl phthalate, 2 parts by weight of triolein, 30 parts by weight of ethanol and 30 parts by weight of ethyl acetate were added into a ball mill, mixed and ball-milled in a planetary ball mill for 5 hours to obtain a casting slurry, the casting slurry was passed through a casting machine to obtain a casting sheet with a thickness of 10 μm, two casting sheets and a piezoelectric ceramic body were laminated and isostatically pressed at 100 MPa in a "sandwich" structure to obtain a green blank;

[0076] The green blank was placed in a microwave sintering furnace and heated to 600°C at a speed of 1°C / min for 2 hours for degreasing. Then, the microwave was turned on and heated to 1050°C at a speed of 10°C / min for 3 hours to obtain a composite ceramic sheet. The frequency and power of the microwave sintering furnace were 2.45 GHz and 1.1 kW respectively.

[0077] Finally, a nickel-copper alloy layer with a thickness of 0.5 μm and a silver layer with a thickness of 0.2 μm were formed on the upper and lower surfaces of the composite ceramic sheet by magnetron sputtering. The magnetron sputtering used a nickel-copper alloy target and a pure silver target with a mass ratio of 1:1. When the vacuum degree of the sputtering studio reached 3×10 -2 Pa, start to fill with argon gas, and adjust the argon gas flow rate to keep the vacuum degree at 8±0.5×10 -1 Pa, the current when sputtering nickel-copper alloy target is 7A, the time is 13 min, the current when sputtering pure silver target is 7A, the time is 6 min, after the single-sided sputtering is completed, the loading fixture is automatically turned over, and the nickel-copper layer and silver layer are sputtered on the other side with the same sputtering conditions.

[0078] The tensile strength of the silver layer was measured to be 18.4 MPa according to the method in 4.5.19 of GJB 3522A-2011.

[0079] Comparative Example 4:

[0080] The same as Example 1, except that [(Na 1 / 2 K1 / 2 ) 0.97 Li 0.03 ]NbO3 replaces [(Na 1 / 2 K 1 / 2 ) 0.97 Li 0.03 ][Nb 0.95 (W 1 / 2 Ce 1 / 2 ) 0.05 ]O 3;

[0081] This embodiment provides a piezoelectric ceramic surface metallization method:

[0082] According to the general formula [(Na 1 / 2 K 1 / 2 ) 0.97 Li 0.03 ] Na2CO3, K2CO3, Li2CO3 and Nb2O5 are weighed in the stoichiometric ratio of NbO3-2wt%LaAlO3-1wt%Fe2O3 and added into a ball mill, and anhydrous ethanol is used as the ball milling medium, and the mixture is mixed and ball milled in a planetary ball mill for 10 hours, and then dried in an oven, and then pre-sintered at 800°C for 2 hours to obtain a preformed powder, and the preformed powder is added into a ball mill, and anhydrous ethanol is used as the ball milling medium, and the mixture is mixed and ball milled again in a planetary ball mill for 10 hours, and then dried in an oven, and a polyvinyl alcohol aqueous solution with a mass concentration of 8wt% is added as a binder and granulated, and the granules obtained after passing through an 80-mesh sieve are added into a mold, and pressed at 100MPa to obtain a piezoelectric ceramic body;

[0083] 40 parts by weight of ferrite NiFe2O4, 8 parts by weight of polyvinyl butyral, 1 part by weight of polyethylene glycol 400, 1 part by weight of butyl benzyl phthalate, 2 parts by weight of triolein, 30 parts by weight of ethanol and 30 parts by weight of ethyl acetate were added into a ball mill, mixed and ball-milled in a planetary ball mill for 5 hours to obtain a casting slurry, the casting slurry was passed through a casting machine to obtain a casting sheet with a thickness of 10 μm, two casting sheets and a piezoelectric ceramic body were laminated and isostatically pressed at 100 MPa in a "sandwich" structure to obtain a green blank;

[0084] The green blank was placed in a microwave sintering furnace and heated to 600°C at a speed of 1°C / min for 2 hours for degreasing. Then, the microwave was turned on and heated to 1050°C at a speed of 10°C / min for 3 hours to obtain a composite ceramic sheet. The frequency and power of the microwave sintering furnace were 2.45 GHz and 1.1 kW respectively.

[0085] Finally, a nickel-copper alloy layer with a thickness of 0.5 μm and a silver layer with a thickness of 0.2 μm were formed on the upper and lower surfaces of the composite ceramic sheet by magnetron sputtering. The magnetron sputtering used a nickel-copper alloy target and a pure silver target with a mass ratio of 1:1. When the vacuum degree of the sputtering studio reached 3×10 -2 Pa, start to fill with argon gas, and adjust the argon gas flow rate to keep the vacuum degree at 8±0.5×10 -1 Pa, the current when sputtering nickel-copper alloy target is 7A, the time is 13 min, the current when sputtering pure silver target is 7A, the time is 6 min, after the single-sided sputtering is completed, the loading fixture is automatically turned over, and the nickel-copper layer and silver layer are sputtered on the other side with the same sputtering conditions.

[0086] The tensile strength of the silver layer was measured to be 24.6 MPa according to the method in 4.5.19 of GJB 3522A-2011.

[0087] Performance Test:

[0088] The surfaces of the piezoelectric ceramics after surface metallization in Examples 1-4 and Comparative Examples 2-4 were polished, polarized for 20 minutes at a DC voltage of 4 kV / mm in silicone oil at 120° C., and then placed for 24 hours as samples to test their performance.

[0089] The room temperature piezoelectric constant of the sample was measured using a ZJ-3AN quasi-static piezoelectric constant tester. d 33 ;

[0090] The electromechanical coupling coefficient kp, mechanical quality factor Qm and dielectric loss tanδ (25°C, 1V, 1kHz) of the samples were measured and analyzed using a precision impedance analyzer (Agilent HP4294A).

[0091] The test results are shown in Table 1 below:

[0092] ;

[0093] As can be seen from Table 1 above, the piezoelectric ceramics of the present invention have excellent piezoelectric properties;

[0094] From the comparison between Example 1 and Comparative Examples 2 and 3, it can be seen that the addition of LaAlO3 and Fe2O3 plays a positive role in improving the piezoelectric properties of piezoelectric ceramics;

[0095] From the comparison between Example 1 and Comparative Example 4, it can be seen that (W 1 / 2 Ce 1 / 2 ) 5+ Doping can maintain the B-site electron conservation state and replace the B-site element Nb, which plays a positive role in improving the piezoelectric properties of piezoelectric ceramics.

[0096] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for metallizing the surface of a piezoelectric ceramic, characterized in that: The details are as follows: S1: preparing a piezoelectric ceramic body; S2: preparing a tape casting slurry containing ferrite, passing the tape casting slurry through a tape casting machine to obtain a tape casting sheet, and laminating the tape casting sheet with a piezoelectric ceramic body and isostatically pressing to obtain a green body; S3: After heating the green blank for degreasing in one stage, heating it to 950-1050°C in two stages and sintering it for 1-5h to obtain a composite ceramic sheet; S4: Finally, a nickel-copper alloy layer and a silver layer are formed on the surface of the composite ceramic sheet by magnetron sputtering; The structural formula of the ferrite is MFe2O4; Wherein M is any one of Cu, Zn, Ni and Co; The casting slurry comprises the following components in parts by weight: 30-50 parts of ferrite, 5-10 parts of polyvinyl butyral, 1-2 parts of polyethylene glycol 400, 1-2 parts of butyl benzyl phthalate, 1-3 parts of triolein, 20-30 parts of ethanol, and 20-30 parts of ethyl acetate; The general chemical structure formula of piezoelectric ceramics is shown below: <h2 style=";text-align:left;direction:ltr">[(Na<h2 style=";text-align:left;direction:ltr"> 1 / 2 <h2 style=";text-align:left;direction:ltr"> K<h2 style=";text-align:left;direction:ltr"> 1 / 2 <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> Li<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> ][Nb<h2 style=";text-align:left;direction:ltr"> 1-y <h2 style=";text-align:left;direction:ltr"> (W<h2 style=";text-align:left;direction:ltr"> 1 / 2 <h2 style=";text-align:left;direction:ltr"> Ce<h2 style=";text-align:left;direction:ltr"> 1 / 2 <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> y <h2 style=";text-align:left;direction:ltr"> ]O3-zwt%LaAlO3-uwt%Fe2O3 Among them, 0<x≤0.1, 0<y≤0.1; 1≤z≤5, 1≤u≤5.

2. The piezoelectric ceramic surface metallization method according to claim 1, characterized in that: x=0.03,y=0.

05.

3. The piezoelectric ceramic surface metallization method according to claim 1, characterized in that: z=2,u=1.

4. The method for metallizing the surface of piezoelectric ceramics according to claim 1, characterized in that: The heating rate of the first stage is 1-5℃ / min, and the heating rate of the second stage is 10-20℃ / min.

5. The method for metallizing the surface of piezoelectric ceramics according to claim 1, characterized in that: The sintering was carried out in a microwave environment.

6. The method for metallizing the surface of piezoelectric ceramics according to claim 1, characterized in that: The mass ratio of nickel to copper in the nickel-copper alloy layer is 1-9:1-9.

7. The method for metallizing the surface of piezoelectric ceramics according to claim 1, characterized in that: The thickness of the nickel-copper alloy layer is 0.5-1 μm, and the thickness of the silver layer is 0.1-0.5 μm.

Citation Information

Patent Citations

  • Ceramic

    AU2011284482A1

  • Ferrite-ceramic composite powder and method of manufacturing the same

    US4952463A